The War's Economic Effects in the Twenty-First Century, Both Locally and Internationally - Rajendra Bapurao Vhatkar; Vishwajeet S.Goswami; Manish Kumar Jaiswal (International Journal of Trends in Humanities, 2025)
The essay looks at how wars in the twenty-first century have affected the economy both theoretically and practically. The idea of the "military economy" is emphasized. Analysis is done on the dynamics of military spending. The causes and forms of conflicts that have taken place in the past and are happening now are explained. Researching the economic effects of Russia's war in Ukraine is emphasized. The pre-war evaluation of nations' potential attested to and validated the belligerent intentions of a big nation that launched an attack on a much smaller one. The subject of protecting minor nations' independence was brought to light by the conflict against Ukraine. The essay's primary goal is to analyze how the conflict has affected the global economy as well as the economies of the involved countries. Inflation, migration, and the volatility of specific commodities markets emerged as the primary mechanisms of the war's impact. As a consequence, many nations' economic growth indices are getting worse. The concerns posed make the global community's task of coming up with innovative ways to deal with war's problems a reality. the essay examines the long-term consequences of modern warfare on international trade, foreign investment, and the stability of global financial systems. It explores how nations redirect resources from developmental and social programs toward defense and military preparedness, often at the expense of human development indicators. The analysis also highlights the ripple effects on employment, supply chains, and regional economic integration. Furthermore, the role of international organizations and alliances in mitigating economic shocks caused by war is discussed. By providing both empirical data and theoretical insights, the essay underscores the importance of strategic economic planning in wartime scenarios and emphasizes that understanding the economic dimensions of conflict is crucial for creating policies that reduce vulnerabilities and enhance resilience.
Keywords: Conflict analysis; Economic Consequences; Global Economy; Military Expenditures; War